2014
DOI: 10.1148/radiol.14132029
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Prophylactic Mastectomy in the American College of Radiology Imaging Network 6667 Trial: Effect of Breast MR Imaging Assessments and Patient Characteristics

Abstract: ).q RSNA, 2014 Purpose:To assess which patient and magnetic resonance (MR) imaging factors are associated with the likelihood of contralateral prophylactic mastectomy (CPM) in patients with newly diagnosed breast cancer. Materials andMethods:The Conclusion:In patients with newly diagnosed breast cancer who underwent breast MR imaging at which a contralateral breast cancer was not identified, patient factors and not breast MR imaging BI-RADS scores were chief determinants in decisions regarding CPM.q RSNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It is out of scope of this study analyzing which factor affect decision of performing CPM in women with newly diagnosed breast cancer. However, accordantly to a prior study [26] young women perceived of greater risk of breast cancer as well as patients with high-risk factors as mutation carries, prior history of chest radiation and family history of breast cancer which could influence the decision maker of CPM. Besides that, following previous study [34,35] index breast cancer characteristics, such tumor size, histology type and nodal status were not predictors of finding occult malignancy in the contralateral breast, avoiding us to make any association of primary tumor and contralateral occult breast malignancy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is out of scope of this study analyzing which factor affect decision of performing CPM in women with newly diagnosed breast cancer. However, accordantly to a prior study [26] young women perceived of greater risk of breast cancer as well as patients with high-risk factors as mutation carries, prior history of chest radiation and family history of breast cancer which could influence the decision maker of CPM. Besides that, following previous study [34,35] index breast cancer characteristics, such tumor size, histology type and nodal status were not predictors of finding occult malignancy in the contralateral breast, avoiding us to make any association of primary tumor and contralateral occult breast malignancy.…”
Section: Discussionmentioning
confidence: 95%
“…The remainder patients went straight to CPM and for all of these three patients, the MRI biopsy was benign and it did not change in the decision of CPM. Other authors also demonstrated that in the CPM setting the patient will undergo to mastectomy independently of the biopsy result that was performed based on MRI recommendations . It is out of scope of this study analyzing which factor affect decision of performing CPM in women with newly diagnosed breast cancer.…”
Section: Discussionmentioning
confidence: 97%
“…A retrospective chart review of 214 patients with DCIS at an academic medical center found that preoperative MRI did not lead to change in the planned surgical management, but that it was associated with increased mastectomy and CPM . Costs, complications, reoperation, and morbidity have also been noted as concerns with aggressive surgery for DCIS …”
Section: Discussionmentioning
confidence: 99%
“…32 Costs, complications, reoperation, and morbidity have also been noted as concerns with aggressive surgery for DCIS. 1,19 In addition to the strength of our large, national sample comprised mostly of community-based settings, recent years of data, and BCSC data which includes women characteristics, this study also has limitations. We were unable to include MRI outcomes in this study, and thus could not determine whether MRI was causative in surgical management plans.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation